Sintomatologia depressiva, autopercepção de saúde e incapacidade em idosos durante a pandemia por COVID-19: um estudo transversal - Pinto, Sara Vasconcelos de Oliveira (2023)
Introduction: Depressive symptoms are manifested by depressed mood and lack of interest in performing activities of daily living. Self-perceived health is a valid and effective measure of general health status for health and physical function problems, used in clinical and epidemiological research. Some evidence, prior to the pandemic, showed the association of depressive symptoms and worse self-perception of health with negative outcomes related to physical function in the elderly. However, we did not observe studies in the literature that explore the relationships of these variables with the disability of community-dwelling elderly, in the context of the COVID-19 pandemic. Objective: To investigate whether there is an association between depressive symptoms and self-rated health and disability in community-dwelling elderly during the COVID-19 pandemic. Methods: This is a cross-sectional study, carried out with community-dwelling elderly people aged 60 years or older living in the State of Ceará. Data collection was carried out through an internet survey and telephone interview (Survey), between October and December 2020. Validated instruments were used to assess depressive symptoms (Center for Epidemiological Studies Depression Scale - CES-D, cutoff ≥16), self-rated health (question from the Brazilian Version of the Quality of Life Questionnaire - SF-36) and disability (World Health Disability Assessment Schedule - WHODAS 2.0 – 12-item version). Sociodemographic issues, internet use, number of comorbidities, perceived social isolation, practice of physical activity, and type of health care were also evaluated. Multiple linear regression models were used to investigate the association of depressive symptoms and self-rated health with disability (5% significance level). Results: A total of 167 elderly individuals with a mean age of 68.2 (±6.8) years were evaluated, 67.5% of whom were female. The mean CES-D score was 16.3 (±7.2) points, with 80 (47.9%) elderly considered to have depressive symptoms; most considered their self-perceived health (SF-36) to be good (55.5%), and the mean score in the WHODAS 2.0 was 19.6 (±7.8) points. In multiple linear regression models, adjusted for covariates, elderly with depressive symptoms (β = 5.69; 95% CI 7.78; 3.59, p < 0.001) and with negative self-perception of health (β = 10, 61; 95% CI 13.94; 7.29, p < 0.001) had higher levels of disability. Conclusion: There was an association of depressive symptoms and self-rated health with disability during the COVID-19 pandemic. These results reinforce the importance of screening for these conditions at an early stage in order to prevent greater levels of disability in this population. In addition, they indicate that functionality is also shaped by psychological factors and that these should be considered in the development of clinical and surveillance strategies for this population.